A escola, o bairro e a cidade: processos de formação de territórios educativos na perspectiva da educação integral - Paulo Felipe Lopes de Carvalho (2014)
This dissertation discusses the relationship between school and territory, considering the openness of the school to its community and to the city within the scope of the Programa Escola Integrada (PEI) developed by the Municipal Secretary of Education (Secretaria Municipal de Educação) of Belo Horizonte-MG. Hence, we aimed to understand whether PEI is able to constitute educational territories and which processes affect these territories. To this end, we chose the qualitative methodology of ethnographic inspiration. The work included a participant observation in a municipal school of Alto Vera Cruz neighborhood, located in the outskirts of Belo Horizonte-MG, as well as the follow-up of a group of teenagers who participated in the experience. Additionally, we conducted group and individual interviews with some educators and proposed the creation of mind maps by students. The research allowed us to understand that between the boundaries (C.Hissa) of the school, the neighborhood and the city, PEI has created an educational geographic area composed of fixed and flows (M. Santos) and as it was appropriated by the subjects of the experience, it made possible the bond between community and neighborhood together with the emergence of collective action through school, with the improvement of the spaces in community and the intensification of a sense of belonging by students and educators through the neighborhood. In this regard, the inclusion of educators in a school that has ties and roots with the territory has provided an educational process closer to the daily life of the students, remaking and questioning the teaching methods. We also noticed that going out to the city provided the students a better understanding of its culture, concerning the relationship between local and global inside the dynamics of PEI. Finally, the research also allowed us to understand that the authority relations are intrinsic to the intersection of the school and the territory, to the extent that, when walking through the neighborhood, we noticed that many groups and individuals seek the appropriation of space, placing the school in a dispute over the use and ownership of this space, which engenders, in the dynamics of PEI, intense processes of (re)territorialization (R. Haesbaert), demanding from professionals an increase awareness concerning this authority relations and conflicts so that they can plan and develop educational activities comprising the territorial dynamics that are processed in the neighborhood. Therefore, the full-time education among bonds, openness, educational activities and authority relations is able to transform the territory into educational territory.